A novel sandwich-type terahertz metasurface sensor integrated ultrathin microfluidic channel for direct detection of aqueous solutions - Cao Yunhao; Sun Hongshun; Song Xubo; Feng Zhihong; Liang Shixiong; Chen Yusa; Ma Lijun; Li Liye; Wu Wengang (Nanophotonics)
A considerable part of the energy of the traditional terahertz metasurface sensor located in the substrate/dielectric layer, which cannot contact and interact with the analyte, resulting in energy loss and greatly limiting the sensitivity of the sensor. In addition, the strong absorption of THz wave by water makes it difficult for THz metasurface sensor to achieve the direct detection of aqueous solution. In this paper, a novel sandwich-type THz metasurface microfluidic sensor with high sensitivity for direct detection of aqueous solution is proposed and verified. Numerical simulation results show the proposed sensor has a perfect absorption peak with high Q-factor of 67.55 and high S of 0.534 THz/RIU at 1.85 THz. The proposed sensor not only can confine all the energy in microfluidic channel greatly improving the energy utilization and light–matter interaction, but also precisely controls the liquid thickness at 3.1 μm greatly reducing the absorption of THz wave, which provides the foundation for realizing the direct detection of aqueous solutions with high sensitivity. Na+ aqueous solutions of different concentrations are selected as analytes to verify the performance and feasibility of the proposed novel sensor. The offset of Na+ aqueous solution with concentrations of 50, 100, 300, 500, 1,000 and 1,500 mmol/L is 13, 22, 46, 60, 93 and 115 GHz, respectively (using pure water as reference). The experiment and simulation of the sensor are basically consistent, which fully verifies the high sensing performance of the designed device and its applicability to the direct sensing of aqueous solution.